Financial contagion in African emerging economies - Ahwireng-Obeng, Asabea Shirley (My University, 2013)
Cannot copy abstract
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Financial crises; Africa; Global markets; Developing countries